Phenomenon of organizational synergy as salvation from crisis situations - E. V. Kozhatkina; A. V. Filyushina (Путеводитель предпринимателя)
In a crisis, resources are often limited and it is only possible to save a business by transforming management. Synergics-managers are able to take the enterprise out ofthe crisis or not to admit it at all. In a synergistic organization it is possible to change the elementary composition and bring it to the desired state, thereby avoiding a crisis. Also, the organization must set a high-quality goalfor success in business. The management ofthe organization itself should contribute to the achievement ofthe goals.